A Study of Social Implications of Access to Justice: Exploring the Impact of Legal Aid on Marginalized Communities (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The laws and the society are closely related and are dependent on each other. The Society is moulded by the laws. However poverty and illiteracy is the antithesis to rule of law as the people of deprived sections of the society are not able to access the privileges and protections provided for them by the Laws and by the State. The availability of legal aid and legal services to the underprivileged has a deep social impact. The National Legal Services Act 1987 has been a game changer in providing access to justice to the marginalised people. However there is much scope for improvement which can be brought about by education and creating awareness and the involving people who are well qualified and public spirited.